Penyebab Pending dan Dispute Klaim Kasus Covid-19 Di Rumah Sakit Tipe B Jawa Tengah 2021 - Nabiila Alunandika, Annisa Hasna; Hidayat, Andi Nur; Yulianti, Laurencia Caprista; Sari, Sofia Nurmala; Ainiyah, Wahyu Qurrotul; Suyoko, Suyoko; Agiwahyuanto, S.Kep.,M.Kes, Faik (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Cases of returning claims for Covid-19 patient care costs from BPJS Health often occur due to administrative and service problems. The number of claim submissions in 2021 was 282 pending files and 67 dispute files. This study analyzes the causes of pending and dispute claims for Covid-19 patient care costs at the Central Java Type B Hospital. The research method is descriptive by observing all (98) pending files and dispute claims for covid-19 cases in 2021. Data collection methods through documentation. Data analysis was carried out using the univariate analysis method. The results of the study show that there are still many obstacles in the service process. Therefore, it needs to be regulated by the provisions of service regulations. As for the claims process, health facilities find it difficult due to dynamic regulatory changes during the pandemic. BPJS health requires certainty in the policy of determining the end of the pandemic period. If Covid-19 benefits are transferred to JKN in the post-pandemic period, the source of financing may not only be done through the conversion of contributions, but there is also an option for assistance funds from the government.